Lakshmibai, Rani of Jhansi, and other essays - Kincaid, C. A. (Charles Augustus), 1870-1954 (SAMP early 20th-century Indian books project ;, 1943)
Essays on Lakshmi Bai, Rani of Jhansi, d. 1858, and on other topics relating to Indian history.